2010
DOI: 10.1194/jlr.m008706
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cholesteryl ester transfer protein activity maintains efficient pre-β-HDL formation and increases reverse cholesterol transport

Abstract: The mechanism by which cholesteryl ester transfer protein (CETP) activity affects HDL metabolism was investigated using agents that selectively target CETP (dalcetrapib, torcetrapib, anacetrapib). In contrast with torcetrapib and anacetrapib, dalcetrapib requires cysteine 13 to decrease CETP activity, measured as transfer of cholesteryl ester (CE) from HDL to LDL, and does not affect transfer of CE from HDL3 to HDL2. Only dalcetrapib induced a conformational change in CETP, when added to human plasma in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 56 publications
3
121
3
Order By: Relevance
“…212 The treatment of hamsters with torcetrapib increased the mobilization of radiolabeled cholesterol from peritoneal macrophages into plasma HDL and subsequent excretion into stool. 213,214 Dalcetrapib: Results of a phase IIb study comparing different doses of dalcetrapib in dyslipidemic patients treated with pravastatin (40 mg/day) indicated a positive effect of dalcetrapib on ABCA1-and SR-BI-mediated cellular cholesterol removal. 215 Likewise, in the dal-ACUTE study that enrolled 300 patients who had a recent ACS, dalcetrapib at a daily dose of 600 mg enhanced the capacity of apoB-depleted plasma to elicit non-ABCA1-specific cholesterol efflux from macrophage foam cells, which was related to changes in apoA-I and HDL-cholesterol levels.…”
Section: Fibratesmentioning
confidence: 99%
See 1 more Smart Citation
“…212 The treatment of hamsters with torcetrapib increased the mobilization of radiolabeled cholesterol from peritoneal macrophages into plasma HDL and subsequent excretion into stool. 213,214 Dalcetrapib: Results of a phase IIb study comparing different doses of dalcetrapib in dyslipidemic patients treated with pravastatin (40 mg/day) indicated a positive effect of dalcetrapib on ABCA1-and SR-BI-mediated cellular cholesterol removal. 215 Likewise, in the dal-ACUTE study that enrolled 300 patients who had a recent ACS, dalcetrapib at a daily dose of 600 mg enhanced the capacity of apoB-depleted plasma to elicit non-ABCA1-specific cholesterol efflux from macrophage foam cells, which was related to changes in apoA-I and HDL-cholesterol levels.…”
Section: Fibratesmentioning
confidence: 99%
“…215 Likewise, in the dal-ACUTE study that enrolled 300 patients who had a recent ACS, dalcetrapib at a daily dose of 600 mg enhanced the capacity of apoB-depleted plasma to elicit non-ABCA1-specific cholesterol efflux from macrophage foam cells, which was related to changes in apoA-I and HDL-cholesterol levels. 216 In normolipidemic hamsters, dalcetrapib promoted the fecal elimination of macrophage-derived cholesterol, 214 but in high-fat-induced hyperlipidemic hamsters the effect was in the opposite direction, with dalcetrapib limiting the excretion of macrophage cholesterol. 217 Dalcetrapib treatment did not restore the reduced ability of HDL from CHD patients to stimulate endothelial nitric oxide production and to inhibit apoptosis and VCAM-1 expression of endothelial cells.…”
Section: Fibratesmentioning
confidence: 99%
“…A study in a hamster model suggested that dalcetrapib promotes reverse cholesterol transport (87). In a human study, among individuals with mean baseline HDL-C and LDL-C levels of 47 mg/dl and 144 mg/dl, respectively, monotherapy with 600 mg of dalcetrapib daily increased HDL-cholesterol levels by 23% compared with placebo administration, after 4 weeks of treatment (88).…”
Section: Mimicking Apo A-i Functionalitymentioning
confidence: 99%
“…Although anacetrapib promotes reverse cholesterol transport and bulk cholesterol excretion in hamsters, some studies suggested that CETP inhibition alone dose not stimulate reverse cholesterol transport (42,43). As suggested, additional effects mediated by the LDL-lowering drug berberine are required (44).…”
Section: Effects On Reverse Cholesterol Transport Of Cetp Inhibitorsmentioning
confidence: 99%